Pengaruh Kemampuan Awal terhadap Hasil Belajar IPA Biologi Peserta Didik Kelas VIII SMP Negeri 1 Kaledupa Kabupaten Wakatobi - Shidik, Muhammad Amran (BIO-EDU: Jurnal Pendidikan Biologi, 2019)
This study discusses fatherly learning about the initial ability of learning outcomes of Biology participants in grade VIII students of SMP Negeri 1 Kaledupa. This research can help educators in preparing teaching materials for students before starting learning. This type of research used in this study is ex post facto. The population in this study were all class VIII of SMP Negeri 1 Kaledupa with a total of 3 classes, while the sample was obtained by 1 class using purposive sampling. The instrument for collecting data uses test instruments for students' initial abilities as well as for learning outcomes. The results of the research show what is meant by Preliminary Principles on the learning outcomes of Biology Science VIII grade students of SMP Negeri 1 Kaledupa. This is based on the results of hypothesis testing using simple regression analysis obtained significance value of 0.004 <0.05. Also, from a simple regression analysis table supported by an initial ability regression coefficient of 0.764 which is claimed to support every 1% of the initial ability score, the added learning outcome score is 0.764. This regression coefficient is positive, so it can be agreed that the direction of the effect of the initial ability variable on learning outcomes is positive.